Thinking through Television. - Lembo, Ron (Cambridge Cultural Social Sciences., 2003)
Investigating American television viewing habits as a distinct cultural form this book is based on an empirical study of the day-to-day use of television by working people and develops a unique theoretical approach to explore the way in which people give meaning to their viewing practices.